2006
DOI: 10.1097/01.brs.0000217620.85893.32
|View full text |Cite
|
Sign up to set email alerts
|

Information and Low Back Pain Management

Abstract: Information based on a biopsychosocial model is recommended in primary care to shift patient beliefs on low back pain. Nevertheless, information delivery alone is not sufficient to prevent absenteeism and reduce healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 31 publications
0
70
0
5
Order By: Relevance
“…Patient information materials, such as leaflets, booklets, books, videos, computer and Internet-based information, have notably increased over the recent years. Most are based on theoretical considerations rather than evidence [13]. Information materials must contain scientifically reliable information and be presented in a form that is acceptable and useful to patients.…”
Section: Patient Education: Definition Educational Interventions Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient information materials, such as leaflets, booklets, books, videos, computer and Internet-based information, have notably increased over the recent years. Most are based on theoretical considerations rather than evidence [13]. Information materials must contain scientifically reliable information and be presented in a form that is acceptable and useful to patients.…”
Section: Patient Education: Definition Educational Interventions Andmentioning
confidence: 99%
“…However, knowledge alone is rarely sufficient for behaviour change [17]. Recent data show that there is conflicting evidence that information positively modifies beliefs on back pain or is efficient in preventing LBP occurrences, recurrences and consequences such as health-care use [13]. Earlier investigations suggested that the Back book, an evidence-based patient educational booklet, improves back beliefs significantly, both fear-avoidance beliefs about physical activity and beliefs about the consequences of back trouble [5].…”
Section: Back Painmentioning
confidence: 99%
See 3 more Smart Citations